WITHDRAWN: Three predictive models for fear of cancer recurrence among recovering breast cancer patients - Zhingjiang Zhou; Chengzhe Zhou; Shibing Guo (2025)
Abstract 15 October, 2025. Research Square has withdrawn this preprint due to overlap with [published work](https://doi.org/10.18282/po3642) by different authors.